Multifactor Productivity and Idea Transmission Channels in the Malaysian Economy - CHAN, Ester Shen Ai (Institutional Knowledge at Singapore Management University, 2009)
This paper examines the contribution of multifactor productivity (MFP) growth to output per worker growth in Malaysia from 1961-2000. MFP growth is found to contribute about 74 percent to output per worker growth from 1987-2000, but has only minimal or negative contribution to growth in the earlier years. This paper then attempts to explain why MFP growth has such a large contribution to output per worker growth in the period 1987-2000 by looking at international trade as channel of technology or idea transfer from the G5 countries into Malaysia. MFP grows because ideas from these advanced nations are transferred into the economy through this channel. Regressions using OLS are carried out on the log-linearized idea production function. The time frame for the regressions is from 1980 to 2000. The empirical results suggest that trade is an important channel through which technology or ideas are transferred into Malaysia, even when other possible channels - foreign direct investment and tertiary education of workers - are controlled for.